2020
DOI: 10.3389/fmed.2020.604919
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking Increased Risk of Overall Mortality in Patients With Non-alcoholic Fatty Liver Disease: A Nationwide Population-Based Cohort Study

Abstract: Background: The evidence suggests a detrimental effect of cigarette smoking on the progression of chronic liver disease. However, the impact of cigarette smoking on mortality among patients with non-alcoholic fatty liver disease (NAFLD) remain unclear.Methods: We used the National Health Examination Survey data collected during 2008–2009 to link the National Death Index to follow-up respondent survival. Diagnosis of NAFLD was based on a lipid accumulation product in participants without significant alcohol use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 45 publications
1
21
0
Order By: Relevance
“…The impact of smoking on NAFLD natural history has been investigated in prospective population-based studies. Analysis from the USA and Thai National Health Examination Surveys revealed that smoking consistently increases mortality by two-fold among NAFLD subjects (HR: 2.33; 95%CI 1.66-3.27) [116][117][118]. Differences were stronger among heavy smoker women (HR for ≥10 packyears: 5.40; 95%CI 2.19-13.4) [118].…”
Section: Impact Of Smoking On Clinical Outcomes In Liver Disease Pati...mentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of smoking on NAFLD natural history has been investigated in prospective population-based studies. Analysis from the USA and Thai National Health Examination Surveys revealed that smoking consistently increases mortality by two-fold among NAFLD subjects (HR: 2.33; 95%CI 1.66-3.27) [116][117][118]. Differences were stronger among heavy smoker women (HR for ≥10 packyears: 5.40; 95%CI 2.19-13.4) [118].…”
Section: Impact Of Smoking On Clinical Outcomes In Liver Disease Pati...mentioning
confidence: 99%
“…Analysis from the USA and Thai National Health Examination Surveys revealed that smoking consistently increases mortality by two-fold among NAFLD subjects (HR: 2.33; 95%CI 1.66-3.27) [116][117][118]. Differences were stronger among heavy smoker women (HR for ≥10 packyears: 5.40; 95%CI 2.19-13.4) [118]. Adjusted by gender, the magnitude of the increase in mortality differed from non-NAFLD population if fatty liver was diagnosed with biochemical tests (hepatic steatosis index) but did not differ if diagnosis was based on US [116,117].…”
Section: Impact Of Smoking On Clinical Outcomes In Liver Disease Pati...mentioning
confidence: 99%
“…All patients with NAFLD, regardless of the presence of T2DM, should avoid alcohol consumption (even moderate) and, when possible, the use of hepatotoxic drugs [ 1 , 2 ]. Clinicians should also recommend avoiding cigarette smoking [ 1 , 2 , 15 , 20 ] and fructose-containing beverages and foods [ 1 , 2 , 15 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the relationship between HNRNPA2B1 expression and the clinicopathological characteristics was statistically analyzed, and the results showed a direct association between HNRNPA2B1 expression and histological grade and metastasis ( Table 2 ). Here, the definition of smoking is as follows: participants who smoked more than 100 cigarettes were classified as smokers ( 36 ). The definition of drinking is as follows: the participant had drunk alcohol regularly (i.e., drank at least once a week on a regular basis) during the past 12 months, otherwise were considered non-drinkers ( 37 ).…”
Section: Resultsmentioning
confidence: 99%